Talking about rape on campus - Zokoza, Babalwa (Rhodes University, 2026)
This study explored undergraduate university men’s perceptions and interpretations of sexual consent, focusing on how these perceptions may reflect broader cultural and societal norms. Understanding these perceptions is crucial for addressing sexual violence, informing consent education and promoting safe, healthy and respectful relationships on campus. The study aimed to explore how men in the university context understand sexual consent. Data was collected using dyad interviews with participants, using vignettes to prompt discussions about consent. The data were then analyzed using Willig’s approach to Foucauldian discourse analysis to identify how societal and cultural influences shape their perceptions. The analysis revealed that the participants generally recognized consent as a mutual, explicit process, ambiguity arose in situations involving intoxication. The findings reveal that societal expectations and traditional gender norms continue to influence how sexual consent is understood. Despite emerging discourses promoting mutual respect and clear communication, traditional notions of male entitlement and female passivity persist, complicating the negotiation of consent. The study suggests that while there is a shift toward more progressive understandings of consent; power dynamics, gendered ideologies, and societal norms continue to shape its interpretation. This research provides valuable insights into the ongoing need for educational interventions to address the complexities surrounding sexual consent and the influence of gendered norms, offering potential pathways for improving consent education and policies within South African university contexts.
a vignette approach to exploring how first-year undergraduate men students at a South African university construct and understand sexual consent
Keywords: Uncatalogued